Mapping of adhesion forces on soil minerals in air and water by atomic force spectroscopy (AFS) - Leite, F. L.; Riul, A.; Herrmann, PSP (Vsp Bv, 2003)
The adhesion force between an atomic force microscope (AFM) tip and sample surfaces, mica and quartz substrates, was measured in air and water. The force curves show that the adhesion has a strong dependence on both the surface roughness and the environmental conditions surrounding the sample. The variability of the adhesion force was examined in a series of measurements taken at the same point, as well as at different places on the sample surface. The adhesion maps obtained from the distribution of the measured forces indicated regions contaminated by either organic compounds or adsorbed water. Using simple mathematical expressions we could quantitatively predict the adhesion force behavior in both air and water. The experimental results are in good agreement with theoretical calculations, where the adhesion forces in air and water were mostly associated with capillary and van der Waals forces, respectively. A small long-range repulsive force is also observed in water due to the overlapping electrical double-layers formed on both the tip and sample surfaces.
Keywords: atomic force spectroscopy; atomic force microscopy; adhesion forces; soil minerals